KNOWLEDGE MANAGEMENT INDICATORS AT THE FACULTY OF INDUSTRIAL ENGINEERING - Inche Mitma, Jorge (2004)
This article deals about the analysis of knowledge management indicators at the Faculty of Industrial Engineering, for the future proposal of a Knowledge Management Model and an Integral Control Board, for controlling the most important capital in an organization, namely intellectual capital.